2021
DOI: 10.1097/mat.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiafiltration Improves Low Levels of Health-Related Quality Of Life (Qol) and Nutritional Conditions of Hemodialysis Patients

Abstract: We compared the effects on the nutritional condition and health-related quality of life (HR-QoL) of the treatment of patients with on-line hemodiafiltration (OL-HDF) and conventional hemodialysis (CHD) using a superflux dialyzer. In total, 47 maintenance (M) HD patients were treated by CHD with a high-flux dialyzer for the first 4 months (1st CHD) and were then switched to predilution OL-HDF for the next 4 months (OL-HDF), after which CHD was resumed for the last 4 months (2nd CHD). We assessed the clinical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…3 For the first time, Savica et al reported an increase in BMI and fat-free mass in patients who had switched from HD to Pre-OL-HDF for 6 months. 16 Several studies found improvement of nutrition and muscular volume in patients treated with Pre-OL-HDF compared with conventional HD, 16,17,18 but Shigematsu et al found no significant differences in muscle mass. 19 One study reported that the higher amino acid losses from the high-exchange volumes used in Pre-OL-HDF worsened body composition.…”
Section: Discussionmentioning
confidence: 99%
“…3 For the first time, Savica et al reported an increase in BMI and fat-free mass in patients who had switched from HD to Pre-OL-HDF for 6 months. 16 Several studies found improvement of nutrition and muscular volume in patients treated with Pre-OL-HDF compared with conventional HD, 16,17,18 but Shigematsu et al found no significant differences in muscle mass. 19 One study reported that the higher amino acid losses from the high-exchange volumes used in Pre-OL-HDF worsened body composition.…”
Section: Discussionmentioning
confidence: 99%
“…46 A total of 11 RCTs reported clinical outcomes, 22,38,39,41,43,44,48,51,53,57 and two were cost-utility analyses of HDF versus HD. 47,50 Fifteen publications were cohort studies, [23][24][25][26][34][35][36][37]42,45,49,52,[54][55][56] of which two reported on HDx 37,54 and the remainder reported on HDF. One cross-sectional study was identified that compared HDF with high-flux HD.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Thirteen publications reported QoL and/or patient-reported outcomes. [35][36][37]41,43,44,[46][47][48]50,51,53,57 Of these, four compared HDF with high-flux HD, 41,44,53,57 with one reporting a statistically significant beneficial effect 44 and three reporting a numerical benefit 41,53,57 in favor of HDF. Three publications compared HDF with HD (flux level not reported) 35,43,47 with one reporting a statistically significant beneficial effect 43 and two a numerical benefit on QoL with HDF.…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations